Poland Syndrome in a Cat - Souza Portella, Ana Clara; Nunes de Santana Castro, Gustavo; Ferreira de Assumção, Romulo (Acta Scientiae Veterinariae, 2025)
Background: Poland Syndrome (PS) is a unilateral teratology of the costosternal portion of the pectoral muscle, breast, subcutaneous tissue, costal cartilages and ribs, with changes in the ipsilateral limb. It is rare, with a higher prevalence in illnesses and in the right hemithorax. The study aims to provide the first correlation of PS in a cat beyond the surgical intervention that involved a pedicled flap of the latissimus dorsi muscle and polypropylene mesh, as well as resolution of the diaphragmatic hernia. Case: The cat was referred for surgical evaluation due to evisceration due to trauma and due to a malformation of the sternum. It was possible to visualize cardiac contractions on the skin in the medial region of the thorax, changes in the right forelimb and in the digital conformation). In addition, the radiograph showed peritoneopericardial hernia. The patient underwent herniorrhaphy surgery and removal of the sternal region. Starting with a median incision from the mid-sternal region to the hypogastric region, dissection of the pericardium and posterior suture and closure of the pericardium with absorbable suture, reestablishment of syntopy of the abdominal organs, suturing of the diaphragm on the entire side between the abdomen and thorax with polypropylene thread. Therefore, the repair of the chest wall was carried out using flaps of the latissimus dorsi muscle dissected in the costal region and translocated through a tunnel in the armpit to the pectoral region, where it was then sutured, occupying all the functions of the external defect. Then, a polypropylene mesh was placed and sutured over the muscles in order to provide greater discomfort and anchor the diaphragm in the abdominal region, finally closing the skin. Discussion: Abnormalities of the unilateral right thoracic region seen in felines include: hypoplasia of the right pectoral muscle, costal cartilages, ribs and ipsilateral digital defects that strongly correspond to Poland Syndrome in humans. Since the pathology is relatively the same for both species, given that mammalian embryogenesis is common, the aforementioned vascular obstructions can lead to similar malformations in both humans and mammals. However, since no similar case has yet been described in animals whose deformities were associated with PS, the present study presents the correlation of this rare syndrome in humans being observed for the first time in a feline. Nevertheless, associated peritoneal-pericardial hernia further highlights the uniqueness of the case. PS in humans is also observed for an aesthetic bias, due to self-esteem and dissatisfaction with physical appearance due to unilateral breast depression, hindering the participation of children and young people in physical activities. However, for animals, the most relevant is the fragility of the thoracic wall, subjecting the organs to potential injuries. As for human surgical techniques, there are a wide variety of possible, including muscle flaps, mainly from the latissimus dorsi muscle, omentum flaps, breast implants, rib and cartilage grafts, and the Marlex mesh are the most commonly used resources. Considering the animal’s quality of life, the surgical technique chosen was the same as that described by Fossum (2014) for reconstruction of the thoracic wall using a polypropylene mesh (Marlex) sutured in the discontinuity of the costal grid and overlapping the pedicled flap of the latissimus dorsi muscle. The only caveat in the present case was the direct contact of the cardiac tissues with the polypropylene mesh, so it was decided to first suture the latissimus dorsi myocutaneous flap and then the mesh. The animal had an uneventful post-surgery period, and the tissues remained stable and healthy to date. Keywords: Poland, feline, syndactyly, diaphragmatic hernia. Título: Síndrome de Poland em gata Descritores: Poland, felino, sindactilia, hipoplasia músculo peitoral, hérnia diafragmática.